2014
DOI: 10.1007/s00216-014-7856-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying silica in filter-deposited mine dusts using infrared spectra and partial least squares regression

Abstract: The feasibility of measuring airborne crystalline silica (α-quartz) in noncoal mine dusts using a direct-on-filter method of analysis is demonstrated. Respirable α-quartz was quantified by applying a partial least squares (PLS) regression to the infrared transmission spectra of mine-dust samples deposited on porous polymeric filters. This direct-on-filter method deviates from the current regulatory determination of respirable α-quartz by refraining from ashing the sampling filter and redepositing the analyte p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 53 publications
1
40
0
Order By: Relevance
“…In preparation for the possible presence of analytical confounders, a more comprehensive use of the infrared spectrum has been preliminarily investigated. [24] This investigation found that the partial least square regression approach may reduce the error associated with the estimation of RCS using the DoF-FTIR technique.…”
Section: Progress Made So Farmentioning
confidence: 99%
“…In preparation for the possible presence of analytical confounders, a more comprehensive use of the infrared spectrum has been preliminarily investigated. [24] This investigation found that the partial least square regression approach may reduce the error associated with the estimation of RCS using the DoF-FTIR technique.…”
Section: Progress Made So Farmentioning
confidence: 99%
“…The backward Monte Carlo unimportant variable elimination identified an optimal subset of wavenumbers exclusively from the α-quartz doublet region (Figure 6, blue features), closely duplicating results from our previous study. 24 Unlike the case for non-coal samples, kaolinite was readily apparent in the IR spectra of coal dust captured on the filter (Figures 3 and 6a). Thus we anticipated that utilizing only features from the quartz doublet region would lead to somewhat reduced accuracy for RCS prediction, i.e., wavenumber selection provided a strong first step in model optimization but left the decision of whether to incorporate kaolinite confounders to the analyst.…”
Section: Resultsmentioning
confidence: 86%
“…This has already been shown to be true for RCS determined in non-coal mine samples. 24 Furthermore, the PLS protocol does not require the analyst to directly interact with the FT-IR spectra by performing band integrations, but considers the individual spectral channels (wavenumbers) automatically when performing a calibration. Therefore, the (blind) prediction of field samples is readily accomplished by transforming the regression coefficients ( q ) into the more familiar form as: b=[bold-italicW]([P]T[W])1q with the following RCS prediction equation as bold-italicyT=[bold-italicX]Tb+g where [ W ] are the PLS loading weights that are discussed in detail elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The essential principle of wrapper methods is to apply variable filters successively or iteratively to sample data until only a 10 desirable subset of quintessential variables remain for PLS modeling (Leardi, 2000;Leardi and Nørgaard, 2004;Weakley et al, 2014 As their name implies, embedded methods nest variable selection directly into the main body of the regression algorithm.…”
Section: Wavenumber Selectionmentioning
confidence: 99%